2001
DOI: 10.2466/pr0.2001.88.3.759
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Coping, and Success among Graduate Students in Clinical Psychology

Abstract: Research has indicated that coping styles and social support are moderating variables in the relationship between stress and distress. Few studies, however, have examined the relationship between these variables and the relative health and success of graduate students in clinical psychology. We administered measures of stress, psychological health, social support, and coping styles to 53 doctoral students in clinical psychology. Current grade point averages were used as a measure of academic success. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
8

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 14 publications
2
45
0
8
Order By: Relevance
“…Individuals who use this coping style tend to be less depressed and more satisfied with their lives. 37 The interview transcripts also indicated that high EI students were able to use their social skills to access their social network in coping with their stress. They were able to use interpersonal skills to address stressful conflicts with colleagues and patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Individuals who use this coping style tend to be less depressed and more satisfied with their lives. 37 The interview transcripts also indicated that high EI students were able to use their social skills to access their social network in coping with their stress. They were able to use interpersonal skills to address stressful conflicts with colleagues and patients.…”
Section: Discussionmentioning
confidence: 97%
“…Low EI students tended to catastrophise on their stressful experiences and make negative inferences from them. Reflection and appraisal may be considered as an emotion-focussed coping style 37 in which emotions evoked by stressful events are reflected upon and appraised to effect a positive reinterpretation of the event. Individuals who use this coping style tend to be less depressed and more satisfied with their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which focused on the psychological processes that occur during the examination collected a baseline measurement immediately before the examination (Eady, 1999;Goldman et al, 1996;Ng et al, 2003). Regardless of research designs, stress reactions, such as changes in mood, in immunological and endocrinological parameters, were consistently observed (Glaser et al, 1991;Kang and Fox, 2001;Maes et al, 1998;Mikulincer, 1989;Nelson et al, 2001;Ng et al, 2003;Sarid et al, 2004;Wolf et al, 1995). Nevertheless, the testing situation is a process, an interaction between a person and an event that crosses time and changing circumstances (Ziedner, 1995).…”
Section: Introductionmentioning
confidence: 91%
“…Araştırmalar stresli durumlarda aktif baş etme stratejilerinin olumlu sonuçlar vermesine karşın (Vitaliano ve diğ., 1987;Holahan ve Moos, 1990;Holahan ve Moos, 1991), kaçınmacı baş etme stratejilerinin uyumu bozucu bir şekilde işlev gördüğüne ve olumsuz psikolojik sonuçları olduğuna işaret etmektedir (Rohde ve diğ., 1990;Holahan ve diğ., 2005;Öngen, 2006). Araştırmalar stresli yaşam olayları karşısında kişiler tarafından benimsenen pasif baş etme stratejilerinin, ergenlerde ve üniversite öğrencilerinde akademik başarıyı olumsuz yönde etkilediğini göstermektedir (Compas ve ark., 2001;Nelson, Dell'Oliver, Koch, Buckler, 2001;Hampel ve Petermann, 2006). Yine pasif baş etme stratejilerinin benlik saygısında düşme, sigara ve alkol kullanımı ve kendine zarar verme davranışıyla ilişkili olduğu görülmektedir (Guinn ve Vincent, 2002;Patterson ve ark., 2004;Park, Armeli, ve Tennen, 2004;McDonald, 2006).…”
Section: Introductionunclassified